Peran Elemen Merek pada Kemasan dalam Membangun Ekuitas Merek: Studi Kasus UMKM Otak-Otak Bandeng Desa Margoanyar - Cindy Anabela; Dayu Nala Rukmi; Aprilia Dwi Lestari (CV. ITTC INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face challenges in building competitiveness, particularly in terms of brand strengthening. One brand element that plays a strategic role but is often underutilized by MSMEs is product packaging. This study aims to understand the role of brand elements on packaging in building brand equity for milkfish otak-otak MSMEs in Margoanyar Village. The study used a qualitative approach with a single case study design. Data were collected through in-depth interviews with MSME owners, non-participatory observation of product packaging, and documentation studies. Data analysis was conducted using a qualitative descriptive method by linking field findings to the concept of consumer-based brand equity. The results show that the application of brand elements on packaging, such as brand name, color, product visuals, and supporting information, plays a role in increasing brand awareness, forming a more positive brand image, and strengthening the perception of product quality. Packaging has proven to be the initial foundation in the process of building brand equity for MSMEs during the business development stage.